Kesesuaian Penggunaan Lahan Pertanian Pada Kawasan Rawan Bencana Kecamatan Selo - Apriani, Santi; Pigawati, Bitta (Jurusan Perencanaan Wilayah dan Kota, 2024)
Selo District is one of the disaster-prone areas in Boyolali Regency. Selo District has a vulnerability to the eruption of Mount Merapi, landslides, and the danger of soil erosion. There are at least 6 out of 10 villages in Selo District that have high disaster vulnerability. The majority of people in Selo District have livelihoods as farmers. In fulfilling food needs, the community began to increase production and expand production areas. To determine the suitability of the use of agricultural land in Selo District, which is in a landslide-prone area, a remote sensing method was carried out through guided classification for primary data acquisition. Analysis was carried out with remote sensing analysis activities through spatial analysis of land use, multiple natural disasters, land capability, suitability of agricultural land use based on land capability, and suitability of agricultural land use in disaster areas. The result is that agricultural land is dominated by suitable land by 62.8% and not suitable by 38.2% with aggravating factors in the form of erosion and landslides.